Investigation of the Experimental Characterization of the Different Inorganic Light Emitting Diodes (LEDS) and the Photovoltaic Effect on These LED - Kamel Remidi; A. Cheknane; M. Haddadi (Institute of Advanced Engineering and Science, 2018)
This paper describes our experiments on the electrical characterization of commercial light emitting diodes of different colors as well as their photoelectric effect. This experiment was conducted at the IMS of Bordeaux, which has a measurement bench allowing the intrinsic characterization of different light-emitting diodes in direct and reverse polarization. This bench also makes it possible to compare these experimental values with the theoretical values obtained by modeling.A second work done at the ENP of El-Harrach allowed us to put in place measurement means to show that there is a photovoltaic effect on the LEDs. For this purpose, we have measured the electrical characteristics of different LEDs and studied their light intensities using an EPLEY pyranometer. This work involved red, green , yellow ,white and blue LEDs. The photovoltaic behavior of light-emitting diodes (LEDs) was studied at ENP D'El Harrah Algeria, for a period of three days in March 2016. LEDs were exposed to solar radiation in the form of unitary units of LEDs. 9-16 hours These irradiated LEDs were monitored for photo-generated voltage and current at one-hour intervals. Solar radiation on a horizontal surface was measured using a Pyranometer.